One Health in human-environment systems: Linking health and the sustainable use of natural resources - Jakob Zinsstag; Joanna Maéva Meyer; Bassirou Bonfoh; Günther Fink; Artemiy Dimov (CABI, 2024)
Abstract Social-ecological system (SES) approaches have been used for strategic analyses of sustainable use of natural resources like rangelands, fishing grounds, livestock or forests. Elinor Ostrom's concept of "governing the commons" contradicts the so called "tragedy of the commons" that assumes that common pool resources are inevitably overused and irreversibly destroyed. We expand the SES to One Health in Social-Ecological Systems (OHSES) by including humans as a resource system that contributes to the human capital of a nation's gross domestic product (GDP). Ill health leads to a reduction of health and wellbeing benefits through premature death, disability or temporary reduction of work capacity. The OHSES analysis framework uses game theory and mathematical modelling for strategy evaluation and comparison. It enables us to analyse the system's current situation and find possible Nash equilibria, Pareto-optimal solutions, and best resource management strategies while maintaining sustainable ecosystem services. A first example on the elimination of dog rabies in Africa shows that when compared to human post-exposure vaccination, coordinated mass dog vaccination is the best strategy for all countries, leading to human capital benefits of US$10 billion over a period of 30 years with the possible elimination of the disease. Inaction and all other strategies have lower welfare benefits and could not lead to the elimination of dog rabies. Further case studies relating human and animal health and sustainable natural resource use are proposed. Epistemological assumptions and ethical issues of a OHSES approach are discussed in the light of pressing needs to combine human and animal health with the sustainable use of natural resources to address the broader impact of the contemporary threats such as antimicrobial resistance, biodiversity loss and climate change. One Health statement This article is a theoretical and methodological contribution to One Health science. It extends the social ecological systems approach of "governing the commons" by Elinor Ostrom through the inclusion of human resources as part of resource system and resource units as One Health in Social-Ecological Systems (OHSES). The concepts of "governing the commons" and "One Health" overlap through the participatory transdisciplinary processes or interactions embedded in both approaches that lead to outcomes or added value for managing shared natural resources and promoting human and animal health. A first case study on the elimination of rabies in Africa is summarized, demonstrating the power of a game theoretical strategy analysis for addressing complex problems of both health and natural resource management. We emphasize system thinking, participatory transdisciplinarity, collective action, equity and gender and the added-value as the main principles of One Health implementation to be evaluated. Several holistic and interdisciplinary approaches exist to safeguard health. Three of the most influential concepts are One Health, EcoHealth, and Planetary Health with actually important differences between them (Lerner and Berg, 2017; Zinsstag et al., 2023a). Here we add a quantifiable framework to the qualitative concept of Health in Social-Ecological Systems (HSES), coined in 2011 (Zinsstag et al., 2011). OHSES encompasses not only human and animal health but also biodiversity, ecology, climate change, agricultural systems, and various social sciences as an integrated systemic mixed quantitative and qualitative approach to relate environmental sustainability and the health of all species.